Cross-sectional analysis between prostate volumes and serum sex hormones in Japanese men attending a urological clinic. (2nd July 2016) - Nukui, Masanori; Takada, Hitosi; Nakagawa, Shuichi
Abstract: Aim : To evaluate epidemiologically the association between measured prostate volume and sex hormones. Methods : Between December 2012 and September 2014, 226 patients attending the urological clinic were assessed for the relationship between prostate volume (PV) and, serum sex hormones, physical size, personal habits, etc. Prostate volume was measured by using transabdominal ultrasonography. Statistically, the Pearson correlation coefficients test was used. Results : Total cases, the cases of PV ≤ 25 ml, and the cases of PV > 25 ml were evaluated respectively. Total cases and the cases of PV > 25 ml showed a positive significant correlation with testosterone (T), but the cases of PV ≤ 25 ml showed no such correlation. The cases of PV > 25 ml had a positive significant correlation with estradiol (E2), but total cases and cases of PV ≤ 25 ml did not. Dehydroepiandrosterone sulfate (DHEAS) showed no correlation with any case of PV, however it decreased significantly with age and had a correlation with alopecia. The E2/T ratio had no correlation with any case of PV, but on the other hand, the T/DHEAS and E2/DHEAS ratios had significant positive correlation with PV > 25 ml. Conclusions : Serum T and E2 had significant positive correlation with measured PV especially in larger prostates. This result seems to correspond with the conventional theory that T and E2 have an etiological effect on benign prostatic hyperplasia. DHEAS did not show direct correlation with PV, however it appeared to suppress the role of T and E2 on benign prostatic hyperplasia growth. DHEAS might be a key to understanding the etiology of benign prostatic hyperplasia with aging.